Fertility of boars of foreign origin - Шаферівський, Б. С. (Scientific Progress & Innovations, 2012)
The following research results have been presented: assessment of sperm quality of large white boars, duroc, landrace and pietrain (German selection) boars. Also the results of research of breeding capacity of large white sows and landrace sows of French origin while crossbreeding with the above mentioned boars of German origin have been stated. Essential difference in concentration, volume, motility of sperm of German origin depending on both breed and season has been ascertained. The most appreciable heterosis effect connected with multi-fertility is shown by crossbreeding of large white sows of French selection with large white boars of German selection.